(untitled) - Maddison, Angus (London, 1970)
The book contains a wealth of agricultural an industrial eficiency, fiscal polivy, protectionism, the use of the price mechanism and direct controls; also an examination of the different types of inflation and instability which have plagued developing countries.
Keywords: Developing countries,Developing countries,Các nước đang phát triển,Các nước đang phát triển; Economic conditions,Economic policy,Điều kiện kinh tế,Chính sách kinh tế